Design and preliminary experimental research on a new biogas fermentation system by solar heat pipe heating - Youzhou, Jiao; Pengfei, Li; Gang, Li; Quanguo, Zhang; Pan, Ding; Shaopeng, Wang; Zan, Gao; Shuangli, Du; Chao, He (International Journal of Agricultural and Biological Engineering, 2016)
Biogas fermentation requires appropriate temperature, while the biogas fermentation can be affected by the low ambient temperature in winter. In order to overcome the negative effects of low temperature fermentation, a new type of solar heat pipe biogas fermentation heating system was designed and a preliminary experiment research on this system was conducted using cow manure as the raw material at 6% concentration and total fermentation volume of 175 L. The experimental results showed that when the system was in normal operation, the fermentation temperature rose every day by gradient. This gradient will gradually become smaller with the increase of fermentation liquid temperature, and the temperature can reach 38°C after stability. Using this solar heat pipe heating system, the fermentation liquid temperature can be increased by 5°C every sunny day. This solar heat pipe heating system plays a significant role in biogas fermentation. The results of economic analysis show that the system can realize the fermentation at constant temperatures of 25°C and 35°C respectively, and it can also save standard coal equivalent of 40 kg and 80 kg in winter and spring, respectively.Keywords: Biogas fermentation, solar heat pipe, heating system, fermentation temperature, economic analysisDOI: 10.3965/j.ijabe.20160902.1935Citation: Jiao Y Z, Li P F, Li G, Zhang Q G, Ding P, Wang S P, et al. Design and preliminary experimental research on a new biogas fermentation system by solar heat pipe heating. Int J Agric & Biol Eng, 2016; 9(2): 153－162.